The traitor - Alexander, V. S. (Kensington Books, 2020)
In the summer of 1942, as war rages across Europe, a series of anonymous leaflets appears around the University of Munich, speaking out against escalating Nazi atrocities. The leaflets are hidden in public places, or mailed to addresses selected at random from the phone book. Natalya Petrovich, a student, knows who is behind the leaflets- a secret group called the White Rose, led by siblings Hans and Sophie Scholl and their friends. As a volunteer nurse on the Russian front, Natalya witnessed the horrors of war first-hand. She willingly enters the White Rose<U+2019>s circle, where every hushed conversation, every small act of dissent could mean imprisonment or death at the hands of an infuriated Gestapo. Natalya risks everything alongside her friends, hoping the power of words will encourage others to resist. But even among those she trusts most, there is no guarantee of safety, and when danger strikes, she must take an extraordinary gamble in her own personal struggle to survive.